npj Digital Medicine - Xie, Yang.; Godfrey, Alan.; Steinhubl, Steven R.; Topol, Eric.; Kvedar, Joseph; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Digital Medicine considers research that explores all aspects of digital medicine including the clinical application and implementation of digital and mobile technologies, virtual healthcare, and innovative applications of artificial intelligence and informatics. The journal aims to guide the transformation of health and healthcare through the incorporation of novel digital and mobile technologies. The journal covers a broad range of topics including but not limited to: Clinical application and efficacy of novel mobile applications, monitors, sensors, software, and wearables Clinical application of novel and validated artificial intelligence and machine learning models Clinical informatics and digital transformation of clinical practice Clinical trials testing the efficacy and interoperability of digital tools and devices Digital medicine ethics, governance, policy, regulation, and security Digital twins Validated digital biomarkers Virtual models of care The journal typically does not consider clinical research using off-the-shelf digital tools and artificial intelligence models, pre-clinical basic science studies, purely observational studies, case studies, and small-scale preliminary studies. The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by digital health experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Biomedical engineering; Medical sciences; Medical care; Medical and Health Technologies; Health Sciences; Health Care